ANALISIS STRATEGI ROS-IN HOTEL DALAM MENGHADAPI PERSAINGAN BISNIS HOTEL DI YOGYAKARTA - , Taufiq Ismail, Dr. Sony Warsono, MAFIS, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was to assess the opportunities of Ros-In Hotel in competing in accordance with its position in the competition, evaluating strategy of Ros-In Hotel. As a result of the many hotels in Yogyakarta, Yogyakartaâs hospitality business competition is very tight, so Ros-In Hotel needs to implement the right strategy in order to compete with rivals in the hospitality industry in Yogyakarta. Stages of the research will be translated into stage frameworks, namely: identifying characteristic of industries in the hospitality business, analyze industry competitors, analyzing the driving forces, analysis of key success factors, internal environment analysis, SWOT formulation, identifying generic strategy and draw conclusions. The results of this study are that Ros-In hotel has a great opportunity to grow and compete despite the threats facing the business as Ros-In Hotel currently has a strategy of cost leadership as a four-star hotel at a price that is cheaper than the other four star hotels in Yogyakarta. Ros-In Hotel has a favorable competitive position that allows them to have aggressive strategies.